A complex four-gene operon containing essential cell division gene pbpB in Bacillus subtilis. - Daniel, R A (1996)
We have cloned and sequenced the promoter-proximal region of the Bacillus subtilis operon containing the pbpB gene, encoding essential penicillin-binding protein PBP2B. The first two genes in the operon, designated yllB and yllC, are significantly similar to genes of unknown function similarly positioned upstream of pbpB in Escherichia coli. Both B. subtilis genes are shown to be nonessential. The third B. subtilis gene, yllD, is essential, as is the correspondingly positioned ftsL gene of E. coli. The predicted product of yllD is similar to FtsL in size and distribution of charged residues but is not significantly related in primary amino acid sequence. The major promoter for the cluster lies upstream of the first gene, yllB, but at least one minor promoter lies within the yllC gene. The operon is transcribed throughout growth at a low level.